2017
DOI: 10.1159/000455008
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Acid Suppression Is Associated with an Increased Risk of Adverse Outcomes in Inflammatory Bowel Disease

Abstract: Background: The intestinal microbiota may influence inflammatory bowel disease (IBD) activity. Histamine 2 receptor antagonists (H2RAs) and proton pump inhibitors (PPIs) can alter the intestinal microbiota. The aim of this study was to assess the relationship between H2RAs, PPIs, and IBD-related outcomes. Methods: We conducted a case-control study of IBD patients using the Veterans Health Affairs databases. Cases were defined by their first instance of an IBD-related hospitalization or surgery and the exposure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 15 publications
0
35
0
Order By: Relevance
“…Regarding IBDs, various observations have led researchers to postulate that chronic PPI administration may have a negative effect on such conditions[129,130]. At present, the data on microbial imbalance during IBD have not been not fully elucidated.…”
Section: Colonmentioning
confidence: 99%
“…Regarding IBDs, various observations have led researchers to postulate that chronic PPI administration may have a negative effect on such conditions[129,130]. At present, the data on microbial imbalance during IBD have not been not fully elucidated.…”
Section: Colonmentioning
confidence: 99%
“…In addition, they also found significant associations between PPIs and mild flares, which suggested that overall acid suppression with implied changes in the intestinal microbiota may be a driving factor. To confirm these associations between PPI use and the outcome of IBD, Shah et al [36] conducted a nested case-control study of patients with IBD within a large, national patient care database. They showed that prescriptions for PPIs were associated with an increased risk of IBD-related hospitalization or surgery in ulcerative colitis patients (adjusted incidence density ratio 1.11, 95% CI 1.02-1.21) and CD patients (adjusted incidence density ratio 1.12, 95% CI 1.02-1.22).…”
Section: Infectious and Inflammatory Diseases Possibly Associated Witmentioning
confidence: 99%
“…11,14,15 Several individual (e.g., male gender) and environmental (e.g., smoking, vitamin D deficiency, NSAID use, PPI use) risk factors have been associated with the risk of IBD or its complications. 2,[16][17][18][19][20][21] High vitamin D levels are a known protective factor for both CD and UC. 18 A range of comorbidities, likely due to a common pathogenesis of immune dysregulation, have also been shown to correlate with IBD, including history of autoimmune disease 22,23 and eosinophilia.…”
Section: Introductionmentioning
confidence: 99%